Implementation of Litigation Mediation in Resolving Medical Negligence Disputes Between Patients and Health Workers - Daffa Ladro Kusworo; Maghfira Nur Khaliza Fauzi (Administrative and Environmental Law Review, 2023)
Negligence in current medical disputes has not yet obtained legal settlement efforts for both parties, either between the patient, the medical staff, or the hospital. Efforts to resolve medical disputes can be done through two methods: litigation and non-litigation mediation. Determining a dispute resolution model with alternative efforts will minimize doctors' worries as well as stimulate medical personnel to improve the health system and existing errors will become an evaluation of health services later, especially also preventing doctors, patients and other parties from being confronted until a court decision actually damages a person's reputation. doctor. Apart from that, it is also an effort to relieve patient conflict, making it possible for patients undergoing treatment to receive reasonable compensation. Medical disputes should emphasize settlement through the ADR route because it not only provides benefits for both parties but also obtains legal guarantees from each party in court in Indonesia. Because when compared to dispute resolution outside the court, litigation mediation offers more integrative offers because it does not require high costs, takes a long time, and does not incline any party by upholding a win-win solution. This study uses a normative legal research method with a statutory and literature study approach and uses descriptive analysis by applying a deductive method. The results of the study show the effectiveness of the implementation of litigation mediation and penal mediation reform in the criminal law system in Indonesia.